The classification of crimes against morality of minors - Семчук, Наталя Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article the author analyzes crimes against morality of minors. On the basis of the conducted analysis of the legislative and theoretical material it is produced the author's denomination of this group of crimes, which encroachon morality of minors - «crimes against morality of minors» and it is proposed additions to the general list of crimes, which are formed this group.